2017
DOI: 10.1590/1678-77572015-0564
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine effects on periodontogenesis: histomorphometrical and immunohistochemical analyses in rats

Abstract: Reports have indicated that serotonin plays an important role in cell migration and differentiation during the organogenesis of several tissues, including the oral types. Administration of selective serotonin reuptake inhibitor (SSRI) drugs during pregnancy could affect the delivery of serotonin to embryonic tissues altering its development. Objective This study aimed to assess the effects of fluoxetine, a selective serotonin reuptake inhibitor, on the formation of the periodontal ligament during pregnancy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
1
4
0
2
Order By: Relevance
“…Absence of cementoblastic lining with some empty cementocytes lacunae and others with pyknotic nuclei was seen. These findings agree with Regueira et al, (2017) who correlated between SSRIs and periodontal cells. They suggested that periodontal cells are sensitive to Fluoxentine “a SSRIs” when taken with a dose 20 mg/kg during pregnancy and lactation and they reported reduction in cementoblasts, fibroblasts and osteoblasts quantities.…”
Section: Discussionsupporting
confidence: 92%
“…Absence of cementoblastic lining with some empty cementocytes lacunae and others with pyknotic nuclei was seen. These findings agree with Regueira et al, (2017) who correlated between SSRIs and periodontal cells. They suggested that periodontal cells are sensitive to Fluoxentine “a SSRIs” when taken with a dose 20 mg/kg during pregnancy and lactation and they reported reduction in cementoblasts, fibroblasts and osteoblasts quantities.…”
Section: Discussionsupporting
confidence: 92%
“…Генералізований пародонтит залишаться однією з гострих проблем сучасної стоматології, й актуальність зумовлена високою поширеністю хвороби за не завжди задовільного ефекту численних засобів і методів, які пропонують для її лікування [4,5]. Саме це зумовило підвищену увагу науковців до пошуку нових патогенетичних методів терапії запальних і запально-деструктивних процесів у тканинах пародонтального комплексу, зокрема ясен [6][7][8][9][10]. Клітинна терапія -інноваційний, надзвичайно перспективний метод лікування хвороб і травм, що дозволяє відновити пошкоджені тканини організму та органи за допомогою трансплантації здорових нових клітин -стовбурових клітин.…”
Section: оригінальні дослідженняunclassified
“…Studies have shown that changes in body's 5-HT levels during embryogenesis caused changes in the growth and development of many tissues, especially in the craniofacial region (Mendes-da- Silva et al, 2002;Santiago et al, 2013;Correia-Leite de Marcelos et al, 2015;Regueira et al, 2017). Reports from Lauder et al (2000) showed that embryos exposed to antagonists of 5-HT2 receptors exhibited different embryological malformations depending on the dose and selectivity of the used antagonist.…”
Section: Introductionmentioning
confidence: 99%